BOOK REVIEW OF THE FAULT IN OUR STARS WRITTEN BY JOHN GREEN - PRADANA, REZA GUSTAV (LANTERN (Journal on English Language, Culture and Literature), 2017)
The purpose of writing this final project is to know the strengths and weakness of The Fault in Our Stars. The writer uses intrinsic elements in analyzing the strengths and weakness and concludes that the strengths of this novel are the theme, characterization, setting of places and symbols, while the weakness of this novel is a male author who writes a female character as point of view. Although the book has a weakness in point of view, but like the other good strengths in the novel, overall, the book is highly recommended to read.Keywords: theme, characterization, setting of places and symbols